Arbitrary pole placement with the extended Kautsky-Nichols-van Dooren parametric form with minimum gain - Schmid, R.; Nguyen, T.; Ntogramatzidis, Lorenzo (Institute of Electrical and Electronics Engineers Inc., 2014)
We consider the classic problem of pole placement by state feedback. We revisit the well-known eigenstructure assignment algorithm of Kautsky, Nichols and van Dooren [1] and extend it to obtain a novel parametric form for the pole-placing feedback matrix that can deliver any set of desired closed-loop eigenvalues, with any desired multiplicities. This parametric formula is then employed to introduce an unconstrained nonlinear optimisation algorithm to obtain a feedback matrix that delivers the desired pole placement with minimum gain.